Consumption of smokeless tobacco and areca nut among adolescents of Bhaktapur, Nepal - Joshi, Ujjwal; Pradhan, Megha; Dahal, Srijana; Tyagi, Krishan Kumar (Journal of Chitwan Medical College, 2020)
Background: Smokeless tobacco use is prevalent in Nepal, and various Smokeless tobacco products are widely available in the country. Areca nut chewing habit is common in Nepal especially in the Terai region adjoining India. This study was aimed to assess the Smokeless Tobacco use and betel nut chewing among adolescents of Bhaktapur and to assess their knowledge about Oral Submucous Fibrosis (OSMF). Methods: Cross-sectional study was performed among adolescents (age group 10-18) years studying in high schools and colleges in Bhaktapur. Random sampling methods was carried out to select 400 adolescents after taking written consent for questionnaire. Descriptive statistical analysis was done using SPSS version 16. Results: Among 400 adolescents, only 24 (6%) admitted to using smokeless tobacco and tobacco based products. One hundred sixty-two (40.5%) participants had experienced betel nut chewing where the most common form was betel nut alone. Sixty one (37.8%) of them had tried at special traditional functions. OSMF was never heard before among 392 (98%) of participants. Conclusions: Smokeless tobacco usage was seen to be less among the participants but areca nut chewing was comparatively high. Traditional functions and predominant usage of betel nut chewing at home emphasizes the need for awareness of harmful effect of betel nut chewing in any forms to be reinforced at one’s home and community. Knowledge about OSMF was seen to be scanty in the adolescents.